Pengembangan media video animasi berbasis audio visual powtoon pada materi siklus air - M. Hadi Satria; Hadi Soekamto; Alfi Sahrina; Dwiyono Hari Utomo (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2023)
This research is motivated by students' needs for animated video media as a support for complex and abstract water cycle material that is difficult for students to understand. This study aims to produce media in the form of animated videos that have superior components in the form of additional material, "Human activities that can affect the water cycle", News Videos and Voice Over language which are based on the development of deficiencies in previous media. This development research only reaches the stage of media feasibility testing using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model and uses formative evaluation to review each stage of development. The validation results on Powtoon animated video media from the material aspect got a percentage of 86 percent and from the media aspect got a percentage of 85 percent. The average of the overall validation test got a percentage of 85 percent which is classified as "Very Feasible". The trial was carried out to 10 students who received a total average of 85.4 percent which was classified as "Very Feasible" which then proceeded to the implementation stage by applying media in the learning process and providing questionnaires to students to get a response in the form of a score and get the final result in the form of an overall average of 82 percent which is classified as "Very Feasible". The main components of this Powtoon animated video media are: 1). News videos got a percentage of eligibility of 85 percent, 2). Additional material "Human activities that can affect the water cycle", got a feasibility of 82 percent, and 3). Voice Over languages, got an eligibility percentage of 86 percent. The results obtained show that the Powtoon animated video media is very feasible to use in the learning process of geography. Penelitian ini dilatarbelakangi kebutuhan siswa terhadap media video animasi sebagai penunjang materi siklus air yang bersifat komplek dan abstrak yang sukar dipahami siswa. Penelitian ini bertujuan menghasilkan media berupa video animasi yang memiliki komponen keunggulan berupa materi tambahan “Aktivitas manusia yang dapat mempengaruhi siklus air”, Video Berita dan bahasa Voice Over yang didasarkan atas pengembangan kekurangan pada media terdahulu. Penelitian pengembangan ini hanya sampai pada tahap uji kelayakan media yang menggunakan model pengembangan ADDIE (Analysis, Design, Development, Implementation, Evaluation) dan menggunakan evaluasi formatif guna meninjau setiap tahapan pengembangan. Hasil validasi pada media video animasi Powtoon dari aspek materi mendapat persentase sebesar 86 persen dan dari aspek media mendapat persentase sebesar 85 persen. Perolehan rata-rata keseluruhan uji validasi mendapat persentase sebesar 85 persen yang tergolong “Sangat Layak”. Uji coba dilakukan kepada 10 siswa yang mendapat rata-rata total sebesar 85,4 persen yang tergolong “Sangat Layak” yang kemudian dilanjutkan ke tahap implementasi dengan menerapkan media dalam proses pembelajaran dan memberikan angket kepada siswa untuk memperoleh respon berupa skor dan mendapatkan hasil akhir berupa rata-rata keseluruhan yaitu sebesar 82 persen yang tergolong “Sangat Layak”. Komponen unggulan media video animasi Powtoon ini yakni; 1). Video berita, mendapat persentase kelayakan sebesar 85 persen, 2). Materi tambahan “Aktivitas manusia yang dapat mempengaruhi siklus air”, mendapat kelayakan sebesar 82 persen, dan 3). Bahasa Voice Over, mendapat persentase kelayakan sebesar 86 persen. Hasil yang diperoleh menunjukkan bahwa media video animasi Powtoon sangat layak untuk digunakan dalam proses pembelajaran geografi.